Elemental and chemical composition of Moringa oleifera husk extracts - Jami, Mohammed Saedi; Ahmad, Mani Malam; Abayomi, Olalere Olusegun; Ngabura, Mohammed (Faculty of Chemical and Natural Resources Engineering,, University Malaysia Pahang, 2019)
Moringa oleifera is a well-known tropical plants with myriads medicinal and nutritional benefits. In this study, the elemental and chemical profiles of husk wastes from moringa plants were spectrometrically elucidated using Liquid Chromatography equipped with an electrospray time-of-flight mass spectrometer (LCMS-QToF) and X-ray Fluorescence analyser. The confirmation of 493 bioactive compounds and two higher concentration of micronutrients indicated the potential of the M. oleifera extracts for medicinal and nutritional purposes. Moreover, the cumulative bioactivities of these chemical and elemental constituents are responsible for the numerous therapeutic functions of moringa husk as reported by many researchers. The elemental and chemical profile could therefore provide lead for future investigation.